2020
DOI: 10.1007/s00217-020-03650-5
|View full text |Cite
|
Sign up to set email alerts
|

Content of selenoaminoacids and catechins in Chinese green teas

Abstract: In this study, famous Zhejiang teas were evaluated as a well-advertised source of selenium. The 25 samples from provinces around China and Asia were purchased in Warsaw tea shops. The speciation analysis of selenium as well as the evaluation of catechin content in water tea infusions was performed using hydrophilic interaction liquid chromatography coupled to mass spectrometry (HILIC-MS/MS). It turned out that all of tested samples can be a great source of organic selenium species (no traces of inorganic selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The chromatogram of water extract of Chinese green tea Lung-Ching (sample 3), under the conditions described earlier [ 29 , 40 ], is presented in Figure 1 B. The analytes were identified by comparing retention times and m/z values obtained by MS and MS 2 mass spectra ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chromatogram of water extract of Chinese green tea Lung-Ching (sample 3), under the conditions described earlier [ 29 , 40 ], is presented in Figure 1 B. The analytes were identified by comparing retention times and m/z values obtained by MS and MS 2 mass spectra ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the previously proposed method for selenium speciation analysis [ 29 , 40 ], where SeMetO was not evaluated, the aqueous component of the mobile phase (ammonium acetate pH 7) was replaced with water. This resulted in the change in the elution order—MeSeCys was eluted before SeMet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the second most widely consumed beverage after water, tea is endowed with high popularity, which is not only due to its great taste but also to its health-promoting properties. 1,2 Catechins (flavan-3-ols), considered as inexpensive, readily applicable, and safe phytochemicals, are the principal bioactive compounds in tea polyphenols. 3 Based on decades of research, burgeoning evidence has confirmed that catechins possess antioxidant, anti-inflammatory, anti-proliferative, anti-angiogenic, and antimetastatic effects by modulating signaling pathways, enzymatic activity, and protein kinases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Natural products from plants traditionally have provided the food industry with one of their most important functions as nutritional supplementation. As the second most widely consumed beverage after water, tea is endowed with high popularity, which is not only due to its great taste but also to its health-promoting properties. , Catechins (flavan-3-ols), considered as inexpensive, readily applicable, and safe phytochemicals, are the principal bioactive compounds in tea polyphenols . Based on decades of research, burgeoning evidence has confirmed that catechins possess antioxidant, anti-inflammatory, anti-proliferative, anti-angiogenic, and anti-metastatic effects by modulating signaling pathways, enzymatic activity, and protein kinases. , The natural structures of catechins are characterized by di- or tri-hydroxyl group substitution of the B ring and the meta-5,7-dihydroxy substitution of the A ring .…”
Section: Introductionmentioning
confidence: 99%